Catecholamines Mediate Multiple Fetal Adaptations during Placental Insufficiency That Contribute to Intrauterine Growth Restriction: Lessons from Hyperthermic Sheep - D. T. Yates; A. S. Green; S. W. Limesand (Journal of Pregnancy)
Placental insufficiency (PI) prevents adequate delivery of nutrients to the developing fetus and creates a chronic state of hypoxemia and hypoglycemia. In response, the malnourished fetus develops a series of stress hormone-mediated metabolic adaptations to preserve glucose for vital tissues at the expense of somatic growth. Catecholamines suppress insulin secretion to promote glucose sparing for insulin-independent tissues (brain, nerves) over insulin-dependent tissues (skeletal muscle, liver, and adipose). Likewise, premature induction of hepatic gluconeogenesis helps maintain fetal glucose and appears to be stimulated by both norepinephrine and glucagon. Reduced glucose oxidation rate in PI fetuses creates a surplus of glycolysis-derived lactate that serves as substrate for hepatic gluconeogenesis. These adrenergically influenced adaptive responses promote in utero survival but also cause asymmetric intrauterine growth restriction and small-for-gestational-age infants that are at greater risk for serious metabolic disorders throughout postnatal life, including obesity and type II diabetes.